Numerical investigation of ballistic performance of shear thickening fluid (STF)-Kevlar composite. (December 2019) - Sen, Subhajit; Jamal M, Noushad Bin; Shaw, Amit; Deb, Arghya
Highlights: Ballistic performance of shear thickening fluid (STF)-Kevlar composite is numerically investigated. Two different composites viz Kevlar-STF-Kevlar layered composite and STF impregnated Kevlar composite are considered. Coupled Eulerian–Lagrangian (CEL) approach is used, wherein Kevlar yarn is modelled using Lagrangian membrane element and STF is embedded in an Eulerian mesh. Computational framework is first validated with available experimental results. Effect of STF in improving the ballistic performance is emphasized. Abstract: Body armors are generally made of several layers of para-aramid fabrics, with Kevlar being the most popular among them. While Kevlar has high strength to weight ratio and sufficient flexibility, the difficulty arises when armors are designed for high threat level. In such cases, ballistic inserts (commonly made of ceramic, metal or composite) are often used in body armor, which make the armor stiffer and bulky. A natural question therefore arises that whether the stiff ballistic inserts can be replaced by something flexible without compromising the strength of the armor. In this context the shear thickening fluid (STF) appears to be an interesting material. The present study is an attempt to numerically investigate the potential of STF in such applications. Towards this, two Kevler-STF composite targets made of Kevlar-STF-Kevlar sandwich composite and STF impregnated Kevlar are considered. Ballistic response of the composite is studied via the coupled Eulerian–Lagrangian (CEL) approach. In the CEL approach, Kevlar yarn is modelled using Lagrangian membrane element and STF is embedded in an Eulerian mesh. Simulations are performed with different projectiles, impact velocities and STF characteristics (shear rate vs viscosity behaviour). In the process the effect of STF in improving ballistic response is brought out.